Long term outcome of treatment of diffuse proliferative glomerulonephritis with pulse steroids and short course pulse cyclophosphamide - S. Bombardieri; L. Carli; A. Tavoni; R. Neri; A. d'Ascanio; M. Mosca; C. Tani (PAGEPress Publications, 2011)
Objectives: To evaluate the long- term outcome of a group of systemic lupus erythematosus (SLE) patients with diffuse proliferative glomerulonephritis (DPGN) treated with pulse steroids and a short course of pulse cyclophosphamide (Cyc) in order to find out baseline predictor variables of disease outcome at the end of the follow-up. Methods: Female SLE patients fulfilling ACR criteria with active DPGN treated with pulse steroids and pulse Cyc were enrolled in the study and retrospectively analyzed with particular interest to renal flares and poor renal outcome at the end of follow- up as outcome measures. Results: 30 female patients with DPGN were included, of these 20 (66,7%) patients are actually in follow-up at our unit, 4 (13.3%) died and 6 (20%) were lost during the follow-up. Fourteen patients (46.6%) presented at least one renal flare (RF) during the follow up for a total of 21 flares. At our last observation, 18 (60%) presented a good renal outcome while 12 (40%) had a poor outcome. Lower age at kidney biopsy resulted an important prognostic factor for the occurrence of both RF and poor long- term renal outcome; additionally, a poor renal outcome resulted significantly correlated with an inadequate response at the end of the protocol and with the number of renal flares after remission. Conclusions: These data suggest that, in general, a short course therapy with Cyc might be effective in controlling disease activity but demonstrated high rate of RF and poor renal outcome over time; however, this protocol might represent an effective therapeutic strategy in a subgroup of patients with specific epidemiological and clinical characteristics and suggest the possibility of tailoring immunosuppressive therapy on the basis of prognostic factor at baseline.